Characterization of ginsenoside compound K metabolites in rat urine and feces by ultra‐performance liquid chromatography with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry. (12th August 2019) - Xie, Tiantian; Li, Zhigang; Li, Bo; Sun, Rongrong; Zhang, Peiying; Lv, Junxiu
Abstract: Ginsenoside compound K (CK) is an active metabolite of ginsenoside and has been shown to have ameliorative property in various diseases. However, the detailed in vivo metabolism of this compound has rarely been reported. In the present study, a method using liquid chromatography quadrupole time‐of‐flight tandem mass spectrometry together with multiple data processing techniques, including extracted ion chromatogram, multiple mass defect filter and MS/MS scanning, was developed to detect and characterize the metabolites of CK in rat urine and feces. After oral administration of CK at a dose of 50 mg/kg, urine and feces were collected for a period of time and subjected to a series of pretreatment. A total of 12 metabolites were tentatively or conclusively identified, comprising 11 phase I metabolites and a phase II metabolite. Metabolic pathways of CK has been proposed, including oxidation, deglycosylation, deglycosylation with sequential oxidation and dehydrogenation and deglycosylation with sequential glucuronidation. Relative quantitative analyses suggested that deglycosylation was the main metabolic pathway. The result could offer insights for better understanding of the mechanism of its pharmacological activities.